Child Labour Issues: Dimensions at Global and India Levels - Venkateswarlu, A. and Ramesh, V. (2008)
Historically, child labour was the preserve of Europe, particularly Britain during the Industrial Revolution; and it has been the phenomenon in the modern period in the developing world. Recently, there have been definitional intricacies, with differentiation in child labour, child work, economically active children and out-of-school children. The dominant factors are poverty and household conditions on supply side and sometimes other demand side pulls. In 1980s and 1990s, the child labour issue has surfaced again. However, child labour has been on the decline both at the global level and in India.